EMPOWERMENT OF WOMEN AND REDUCING HOUSEHOLD POVERTY: NANGARAHAR PROVINCE, AFGHANISTAN - Fathullah Shinwari; Hayatullah Ashna; Niamatullah Hayat (International Journal of Contemporary Issues in Social Sciences, 2024)
The main aim of the study was to identify various income generating activities of women in the area of Nangrahar province, Afghanistan. The study also aims to assess the contribution of women into their household income and to identify various socio economics problem faced by women while engaged in their income generating activities. For this purpose, primary data was collected from a sample of eighty households. It was found that people of the research area were quite rigid and traditionally bound and mostly women were thus not allowed to work outside their home, due to cultural and religious constraints, still women were contributing sufficiently in their household income besides performing their household chores. The study also found that in most cases decision made by males rather than females. They were of the view that their financial contribution was a key factor in strengthening their economics status, social contacts, saving and decision making power. It is therefore, recommended that more educational facilities in general be provided in the study area which may help in allowing women to be involved on larger scale in income generating activities that they doing in present. The study also recommended that women organization should be formed and training facilities should be provided to women so that they could be involved in a better way in income generating activities. It is also suggested that credit facilities be provided to women to improve their socio economics condition.